2015
DOI: 10.1039/c5ta00244c
|View full text |Cite
|
Sign up to set email alerts
|

Simple one-step synthesis of fluorine-doped carbon nanoparticles as potential alternative metal-free electrocatalysts for oxygen reduction reaction

Abstract: Fluorine-doped carbon nanoparticles were successfully synthesized via a simple one-step solution plasma process at room temperature and atmospheric pressure without the addition of a metal catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
125
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(131 citation statements)
references
References 55 publications
6
125
0
Order By: Relevance
“…In such systems, the plasma enables unique reactions such as C–H activation reactions at the interface between the solution and plasma, whereas conventional plasma induces random decomposition reactions. We have fabricated graphene, heterographene, nanocarbon sheets, and nanocarbon spheres via solution plasma from organic solutions containing solvents such as benzene, toluene, pyridine, or pyrazine60616263646566676869707172. Moreover, the reaction rate is substantially higher than the rates of other synthesis methods such as chemical vapor deposition and pyrolysis synthesis.…”
mentioning
confidence: 99%
“…In such systems, the plasma enables unique reactions such as C–H activation reactions at the interface between the solution and plasma, whereas conventional plasma induces random decomposition reactions. We have fabricated graphene, heterographene, nanocarbon sheets, and nanocarbon spheres via solution plasma from organic solutions containing solvents such as benzene, toluene, pyridine, or pyrazine60616263646566676869707172. Moreover, the reaction rate is substantially higher than the rates of other synthesis methods such as chemical vapor deposition and pyrolysis synthesis.…”
mentioning
confidence: 99%
“…[12,[14][15] Panomsuwan et al reported the incorporation of fluorine (F/C = 0.05 on surface) in CNPs by solutionp lasma in C 6 H 5 CF 3 ; [14] the affinity of these CNPs to water was not mentioned. [12,[14][15] Panomsuwan et al reported the incorporation of fluorine (F/C = 0.05 on surface) in CNPs by solutionp lasma in C 6 H 5 CF 3 ; [14] the affinity of these CNPs to water was not mentioned.…”
mentioning
confidence: 99%
“…[19] Unlike the case of hydrophilic CNPs produced from B/W bilayer solution, [17] CNPs(W)d id not have ah ydrophilic group such as OH. [14] Large numbers of CÀFb onds were incorporated into the surfacea sw ell as inside the CNPs. [19] Judging from the appearance of the Db and (1360 cm À1 )a nd Gb and (1580 cm À1 )i nR aman spectra (Figure 2c), and the intensity ratio of those bands (I D /I G = 1), both CNPs shouldh ave disordered structures.F urther,X -ray diffraction (XRD) patterns of CNPs ( Figure S2) showed broad diffraction peaks (2q % 228 and 418)c orresponding to amorphous carbon by analogy to the previous report.…”
mentioning
confidence: 99%
“…25) Thus, the in SP process, it is very important to select suitable raw materials to control the synthesis rate of the nanocarbons. Moreover, the doping of different elements, such as B, 5) N, 26,27) F, 5) and Cl, 28) or multiple dopants 29,30) into the carbon matrix can be easily realized by the SP process using suitable organic solvents as raw materials. The N-doped nanocarbon materials showed higher oxygen reduction reaction (ORR) activity than nondoped and other heteroatomdoped nanocarbon materials.…”
Section: )mentioning
confidence: 99%
“…Electric discharge in liquid media is a versatile method for the synthesis of metal nanoparticles, [1][2][3] bimetallic nanoparticles, 4) nonmetal catalysts, [5][6][7] carbon nanospheres (CNS), 8) graphenes, 9) carbon nanotubes, [10][11][12][13] carbon onions, 14) metal nanoparticles covered by carbon, 15,16) mesoporous silica, 17) and polymers. 18) Among these, nonmetallic carbon catalysts have attracted a great deal of attention as a Pt substitute material in energy storage devices such as secondary batteries 19) and supercapacitors 20,21) for smart grids or electric automobiles.…”
Section: Introductionmentioning
confidence: 99%